A Seasonal Tourism During the COVID-19 Pandemic in Parapat, Lake Toba: Seasonal Tourism During the COVID-19 Pandemic in Parapat, Lake Toba - Saragi, Alexander Adrian (Jurnal Koridor, 2022)
Parapat is a village in Girsang Sipangan Bolon District, Simalungun Regency. In the Master Plan of Priority Tourism Destinations (RIDPP) of Lake Toba 2020-2045, Parapat became one of the Key Tourism Area (KTA) in supporting Lake Toba Tourism Priority Destination (DPP). DPP Lake Toba is one of ten DPP that the government has set in achieving tourism development goals. So that the government is aggressively developing tourism in Indonesia to be increasingly known both nationally and internationally, tourism development is more directed towards sustainable tourism development. The indicators assessed in this study are on seasonal tourism issues, which refers to the Baseline Indicators of Sustainable Tourism Development for Tourism Destinations by WTO. This research uses qualitative research with a descriptive approach. Award chose qualitative descriptive research because this study explores the assessment of seasonal tourism indicators in Parapat that will be presented in descriptive form. The results of the study analysis found that there was an increase in the number of tourist visits to Parapat. This is due to the many meeting activities and MICE held at the hotel both by various government agencies and the local agency area. Regarding tourist attractions, the Lake Toba Festival cannot be held because of the enactment of PPKM rules in Parapat. In response to the COVID-19 pandemic situation in 2020, all lodging establishments, restaurants, and attractions implement strict health protocols. Some hotels will have to take a policy to close their businesses until June temporarily. However, in July, they reopened their business with a low room occupancy rate. In addition, there are several implementations of health protocols in the dining establishment that must be applied to every dining business in Parapat, such as maintaining distance and providing a sink for visitors.